GGT1 is a SNP eQTL gene involved in STAT3 activation and associated with the development of Post-ERCP pancreatitis - Furukawa, Ryutaro; Kuwatani, Masaki; Jiang, Jing-Jing; Tanaka, Yuki; Hasebe, Rie; Murakami, Kaoru; Tanaka, Kumiko; Hirata, Noriyuki; Ohki, Izuru; Takahashi, Ikuko; Yamasaki, Takeshi; Shinohara, Yuta; et al. (Scientific reports, 2024)
Post-ERCP pancreatitis (PEP) is an acute pancreatitis caused by endoscopic-retrograde-cholangiopancreatography (ERCP). About 10% of patients develop PEP after ERCP. Here we show that gamma-glutamyltransferase 1 (GGT1)-SNP rs5751901 is an eQTL in pancreatic cells associated with PEP and a positive regulator of the IL-6 amplifier. More PEP patients had the GGT1 SNP rs5751901 risk allele (C) than that of non-PEP patients at Hokkaido University Hospital. Additionally, GGT1 expression and IL-6 amplifier activation were increased in PEP pancreas samples with the risk allele. A mechanistic analysis showed that IL-6-mediated STAT3 nuclear translocation and STAT3 phosphorylation were suppressed in GGT1-deficient cells. Furthermore, GGT1 directly associated with gp130, the signal-transducer of IL-6. Importantly, GGT1-deficiency suppressed inflammation development in a STAT3/NF-κB-dependent disease model. Thus, the risk allele of GGT1-SNP rs5751901 is involved in the pathogenesis of PEP via IL-6 amplifier activation. Therefore, the GGT1-STAT3 axis in pancreas may be a prognosis marker and therapeutic target for PEP.